1993
DOI: 10.1210/endo.133.6.8243315
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the inhibitory effects of iodide on thyroid cell proliferation are due to arrest of the cell cycle at G0G1 and G2M phases.

Abstract: The thyroid gland is unique in its ability to respond to ambient levels of iodine to autoregulate thyroid function and, possibly, thyroid cell proliferation. Although the inhibitory effects of iodide on thyroid cell proliferation have been previously reported, the exact mechanism and site of action of iodide on cellular proliferation events are poorly understood. Our initial experiments established the optimal cell plating density and timing to achieve exponential cell growth of FRTL5 thyroid cells, and subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 35 publications
6
22
1
Order By: Relevance
“…These data agree with previous results showing that, in thyroid FRTL-5 cells, iodide induces cell cycle arrest in both G1 and G2/M phases (Smerdely et al 1993). The p53 protein can regulate the G 1 or G 2 /M transition by inducing p21, an inhibitor of cyclin/cyclin-dependent kinase (CDK) complexes (Roninson 2002).…”
Section: Discussionsupporting
confidence: 92%
“…These data agree with previous results showing that, in thyroid FRTL-5 cells, iodide induces cell cycle arrest in both G1 and G2/M phases (Smerdely et al 1993). The p53 protein can regulate the G 1 or G 2 /M transition by inducing p21, an inhibitor of cyclin/cyclin-dependent kinase (CDK) complexes (Roninson 2002).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast the inhibition of proliferation induced by NaI is associated with more cells in the G2 and post-G2 'endoreduplication' populations. These data suggest that cell-cycle blockade (at G2/M) and endocycle escape contribute to the mechanism of inhibition, and are in agreement with studies from Smerdely et al (1993), who demonstrated significant reduction in TSH-induced proliferation by 100 mM NaI. This was attributable to accumulation of the cells both in G0/G1 and G2/M.…”
Section: Discussionsupporting
confidence: 91%
“…Iodide inhibits thyroid adenylate cyclase producing a reduction in TSH-or forskolin-stimulated cAMP production in several species (Van Sande et al 1985). Although this, in itself, would have a negative impact on thyrocyte growth, it is unrelated to the G2/M arrest in the cell cycle of FRTL-5 induced by iodide (Smerdely et al 1993(Smerdely et al , 1995. Iodide has also been demonstrated to induce apoptosis in a thyroid cell line via a p53 independent mechanism (Vitale et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The irregular shaped nuclei with chromatin aggregates observed in the thyrocytes of the AMD groups have also been observed in other tissues such as rat hepatocytes exposed to AMD (20). AMD may induce apoptosis either directly, or indirectly by virtue of the high levels of iodide in the drug, as shown by Smerdely et al (21). In our experiments, apoptosis was not evident at the level of iodide used here, suggesting that the effects observed with AMD are not primarily related to the iodine content of the drug alone (22,23).…”
Section: Discussionsupporting
confidence: 59%